Analysis of Policies and Strategies to Lower Childhood Stunting in South Sulawesi, Indonesia - Paikah, Nur; Yamin, Muhammad; Hafni, Nur (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Analysis of policies and strategies to accelerate stunting reducing in children in South Sulawesi Province. Examine the facts and make corrections to various policies and strategic programs that are better and more comprehensive by the central government and regional governments because the quality of future human resources is largely determined by the current condition of children so that the golden generation of 2045 can be realized. This research aims to analyzing policies to reduce stunting rates in South Sulawesi Province. The research uses normative legal methods analyzed with policy theory, while data collection techniques come from trusted sources such as government reports, scientific journals and health survey data. The research findings reveal several important factors contributing to the high stunting rates in South Sulawesi Province, including limited access to adequate nutrition, low maternal education levels, and poor sanitation. Evaluation of existing policies indicates that the policies implemented by the provincial government have had a positive impact but still require improvement and enhancement in their implementation. Therefore, recommended strategies to accelerate stunting reduction include improving access to adequate nutrition, enhancing maternal health education, and improving sanitation. The results of this study are expected to provide input to the provincial government and relevant stakeholders in formulating more effective and efficient policies to address stunting in children in South Sulawesi Province.